Harmonious impacts of allelopathic bacteria with chemical herbicides for sustainable production of wheat (Triticum aestivum L.) under wild oat (Avena fatua L.) infestation - Muhammad Tauseef Jaffar; Zahir Ahmad Zahir; Jianguo Zhang; Abubakar Dar; Muhaimen Ayyub; Hafiz Naeem Asghar (Italian Journal of Agronomy)
Weeds are one of the major limiting factors for wheat production. So, a study was conducted to integrate allelopathic bacteria with reduced dose of chemical herbicide for sustainable wheat production in wild oat infestation. Cyanide-producing Pseudomonas strains were applied in four combinations with and without two chemical herbicides (Axial and Atlantis) at 25% and 50% recommended dose under axenic conditions. Results showed that C4 combination significantly reduced growth and development of wild oat under 50% Axial while increase wheat growth. Afterward, C4 combination and Axial herbicide were selected for field evaluation, where it reduced the weed density (82.1%), SPAD value (26.0%) and grain yield (88.2%) under 75% Axial, and relative wild oat density (70.9%), photosynthetic rate (26.6%) and transpiration rate (25.6%) under 50% Axial in wild oat. While C4 combination improved SPAD value (26.9%), shoot length (10.1%), tillering (33.3%), biological yield (32.7%), straw yield (24.4%), grain yield (46.8%), transpiration rate (9.6%) and stomatal conductance (14.7%) in wheat under 75% Axial. The increase in growth and yield of wheat was found at par with C4 under 50% and 75% Axial. Thus, it is concluded that allelopathic bacteria could be used with 50% Axial for sustainable wheat production under wild oat.